Водяна та прибережно-водяна рослинність Шацького Поозер’я - Кузярін, Олександр Тимофійович; Кузьмішина, Ірина Іванівна; Коцун, Лариса Олександрівна; Коцун, Борис Борисович; Матейчик, Василь Іванович; Kuziarin, Oleksandr T.; Kuzmishyna, Iryna I.; Kotsun, Larysa O.; Kotsun, Borys B.; Mateichyk, Vasyl I. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Basing on the analysis of the phytocenotic records and references the aqueous and coastal-aqueous vegetation classificate scheme by ecologo-floristic method of Braun-Blanqe for the Shatsk Lake Land was elaborated. The syntaxonomic composition of the research vegetation includes 7 classes, 12 orders, 23 alliances, 76 associations and 1 basal communities.
Keywords: Shatsk Lake Land; vegetation; classificate scheme; association